The Effects of Physical Education Class Participation and Perception on Stress and School Life Adaptation - 박순문; 이하언 (International Journal of Advanced Culture Technology(IJACT), 2023)
The purpose of this study is to investigate the relationship between stress and school life adaptation according to the degree of participation in physical education class and perception of middle school students. In order to achieve this research objective, the subjects of this study were sampled using cluster random sampling from male and female students attending middle schools in Gwangju Metropolitan City and Jeollanam-do in 2020. 150 males and 150 females, a total of 300 people were sampled. The statistical analysis used for data analysis was frequency analysis, exploratory factor analysis, reliability analysis, and multiple regression analysis using SPSS Windows 21.0 Version. The conclusions obtained in this study through data analysis by such methods and procedures are as follows. First, it was found that middle school students' participation in physical education classes and perceptions had a partial effect on stress. Second, it was found that the degree of participation and awareness of middle school students' physical education class had a partial effect on their adaptation to school life. Third, middle school students' stress was found to have a partial effect on school life adaptation.